2016
DOI: 10.1007/s00039-016-0388-1
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian isotopy of tori in $${S^2\times S^2}$$ S 2 × S 2 and $${{\mathbb{C}}P^2}$$ C P 2

Abstract: Abstract. We show that, up to Lagrangian isotopy, there is a unique Lagrangian torus inside each of the following uniruled symplectic fourmanifolds: the symplectic vector space R 4 , the projective plane CP 2 , and the monotone S 2 × S 2 . The result is proven by studying pseudoholomorphic foliations while performing the splitting construction from symplectic field theory along the Lagrangian torus. A number of other related results are also shown. Notably, the nearby Lagrangian conjecture is established for T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…We construct a Hamiltonian diffeomorphism with support near the sphere ∂B(3) displacing L(1, 2) ∪ L(2, 1) from a neighborhood of the cylinder T . This is equivalent to constructing a Hamiltonian isotopy of L(1, 2) ∪ L(2, 1), where the Lagrangian tori remain close to ∂B (3). It is convenient to use symplectic polar coordinates (R 1 , θ 1 , R 2 , θ 2 ) where…”
Section: Construction Of ψmentioning
confidence: 99%
See 1 more Smart Citation
“…We construct a Hamiltonian diffeomorphism with support near the sphere ∂B(3) displacing L(1, 2) ∪ L(2, 1) from a neighborhood of the cylinder T . This is equivalent to constructing a Hamiltonian isotopy of L(1, 2) ∪ L(2, 1), where the Lagrangian tori remain close to ∂B (3). It is convenient to use symplectic polar coordinates (R 1 , θ 1 , R 2 , θ 2 ) where…”
Section: Construction Of ψmentioning
confidence: 99%
“…Our proof concludes as follows. First, by [3], Theorem B, we can apply a Hamiltonian isotopy of T * T 2 mapping L(1, 2) to a constant section. Composing with a translation in the fiber we get a global symplectomorphism φ of T * T 2 with φ(L(1, 2)) = O, the zero section.…”
Section: Proofmentioning
confidence: 99%
“…Notably, Shevchishin [31] and Nemirovski [29] have shown that the standard symplectic vector space false(C2,ω0false)$(\mathbb {C}^2,\omega _0)$ does not admit a Lagrangian embedding of the Klein bottle. The author together with Goodman–Ivrii showed that any Lagrangian torus inside the symplectic vector space must be unknotted [10].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Shevchishin [She09] and Nemirovski [Nem09] have shown that the standard symplectic vector-space (C 2 , ω 0 ) does not admit a Lagrangian embedding of the Klein bottle. The author together with Goodman-Ivrii showed that any Lagrangian torus inside the symplectic vector space must be unknotted [DRGI16].…”
Section: Introductionmentioning
confidence: 99%